Constraining oceanic oxygenation during the Shuram excursion in South China using thallium isotopes. Issue 3 (3rd February 2020) - Fan, Haifeng; Nielsen, Sune G.; Owens, Jeremy D.; Auro, Maureen; Shu, Yunchao; Hardisty, Dalton S.; Horner, Tristan J.; Bowman, Chelsie N.; Young, Seth A.; Wen, Hanjie
Abstract: Ediacaran sediments record an unusual global carbon cycle perturbation that has been linked to widespread oceanic oxygenation, the Shuram negative C isotope excursion (NCIE). However, proxy‐based estimates of global ocean redox conditions during this event have been limited largely due to proxy specificity (e.g., euxinic sediments for Mo and U isotopes). Modern global seawater documents a homogenous Tl isotope composition (ε 205 Tl = −6.0) due to significant manganese oxide burial, which is recorded in modern euxinic sediments. Here, we provide new data documenting that sediments deposited beneath reducing but a non‐sulfidic water column from the Santa Barbara Basin (ε 205 Tl = −5.6 ± 0.1) also faithfully capture global seawater Tl isotope values. Thus, the proxy utilization of Tl isotopes can extend beyond strictly euxinic settings. Second, to better constrain the global redox conditions during the Shuram NCIE, we measured Tl isotopes of locally euxinic and ferruginous shales of the upper Doushantuo Formation, South China. The ε 205 Tl values of these shales exhibit a decreasing trend from ≈−3 to ≈−8, broadly coinciding with the onset of Shuram NCIE. There are ε 205 Tl values (−5.1 to −7.8) during the main Shuram NCIE interval that approach values more negative than modern global seawater. These results suggest that manganese oxide burial was near or even greater than modern burial fluxes, which is likely linked to an expansion of oxic conditions. This ocean oxygenation may have been an important trigger for the Shuram NCIE and evolution of Ediacaran‐type biota. Subsequently, Tl isotopes show an increasing trend from the modern ocean value to values near the modern global inputs or even heavier (ε 205 Tl ≈ −2.5 ~ 0.4), occurring prior to recovery from the NCIE. These records may suggest that there was a decrease in the extent of oxygenated conditions in the global oceans during the late stage of the Shuram NCIE.